Predicting mental health of people living with HIV/AIDS (PLWHA): the role of psychosocial factors (2005)
This study examined the influence of self-esteem, health locus of control, age and. social support in predicting the mental health of people living with HIV/AIDS. Participants were made up of one hundred and three (103) purposively selected PLWHA; 56 males and 47 females whose ages ranged between 16-60 years with a mean age or 29.52 and standard deviation of 7.96. The ex-post facto research design was employed while data was collected with the aid of a questionnaire divided into 5 sections with each section measuring a variable. Result of a multiple regression analysis indicated that self-esteem, health locus of control, age and social -support significantly co-predict mental health of PLWHA (F (4, 88)=65.09, p<. 01). While all the psychosocial variables regressed with the exception of health locus of control independently predicted mental health of PLWHA. T-test result showed that there is no sex difference in PLWHA's mental health, t=0.14, df 101, p>.05. Thus, it is recommended that treatment emphasis of PLWHA should not only be on chemotherapy regimen, significant others should be incorporated in the medical care while other psychological programmes should form part of the overall therapy.